2006
DOI: 10.1158/1055-9965.epi-06-0020
|View full text |Cite
|
Sign up to set email alerts
|

Body Size, Physical Activity, and Risk of Hodgkin's Lymphoma in Women

Abstract: Few studies have examined the associations of body size and physical activity with the development of Hodgkin's lymphoma (HL) in women. In data from a population-based case-control study in women ages 19 to 79 years, we assessed the relation of self-report height, weight, body mass index (BMI), and strenuous physical activity to HL risk in 312 cases with diagnostic re-review and 325 randomdigit dialed controls using logistic regression. Analyses were stratified by age group and tumor cell presence of EBV. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 44 publications
2
32
0
2
Order By: Relevance
“…Nevertheless, a reduced risk of leukemia/lymphoma was shown, and the results are in line with previous observations (26,27). Although the decrease in cancer risk was significant only for athletic groups with moderate intensity levels, the trend seems present for all subgroups, except for that of the low lifetime activity level.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, a reduced risk of leukemia/lymphoma was shown, and the results are in line with previous observations (26,27). Although the decrease in cancer risk was significant only for athletic groups with moderate intensity levels, the trend seems present for all subgroups, except for that of the low lifetime activity level.…”
Section: Discussionsupporting
confidence: 91%
“…Table 1 presents the main characteristics and results of the 15 cohort studies (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and eight case-control studies (18)(19)(20)(21)(22)(23)(24)(25) included. Three studies investigated more than one physical activity domain (19,24,40) and nine studies provided results stratified by gender (20,22,23,25,26,29,32,39,40).…”
Section: Resultsmentioning
confidence: 99%
“…If risk estimates were provided for different numbers of adjustment factors, the maximally adjusted risk estimate was used. If a study presented several risk estimates for physical activity at various time periods in life, the risk estimate for the most recent time period was chosen (21,22,34) as most studies provided risk estimates for recent physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The 7 case-control studies included a total of 5,229 non-Hodgkin lymphoma cases, 366 Hodgkin lymphoma cases, and 26,403 control subjects (28,(30)(31)(32)(33)(34)(35). In the 5 prospective cohort studies, a total of 5,858 nonHodgkin lymphoma cases and 58 Hodgkin lymphoma cases were identified among a total of 3,154,781 subjects (29,(36)(37)(38)(39).…”
Section: Study Characteristicsmentioning
confidence: 99%